The project bases of Ukrainian transport infrastructure development - Pokhylchenko, O. (Видавництво Львівської політехніки, 2014)
The article formed the project bases of Ukrainian transport infrastructure. The critical overview of present and promising projects on the development of major Ukrainian transport industry sectors are provided. In particular, it detects the problems inherent in automobile, railway, shipping and aviation industry sectors, as well as in road and transport system in general. The role of international financial institutions such as EBRD and IBRD in funding various infrastructural projects is outlined and their detailed characteristics are provided. Among the priorities of road and transport system development, the establishment of international transport routes and transport-warehouse complexes, designed for the purpose of processing containerized, piggyback and other types of freight, are highlighted. Cформовано проектні засади розвитку транспортної інфраструктури України. Подано критичний огляд існуючих та перспективних програм розвитку основних транспортних галузей України. Зокрема, виявлено проблеми, характерні для галузей автомобільного, залізничного, водного, повітряного транспорту, а також загалом дорожньо-транспортного комплексу. Підкреслено роль міжнародних фінансових інститутів, передусім ЄБРР та МБРР, у фінансуванні інфраструктурних проектів та подано їх детальну характеристику за напрямом “Автомагістралі”. Серед пріоритетних напрямів розвитку транспортно-дорожнього комплексу виділено створення міжнародних транспортних коридорів та транспортно- складських комплексів, призначених для переробки контейнерних, контрейлерних та інших вантажів.
Проектні засади розвитку транспортної інфраструктури України
Keywords: logistics; logistic infrastructure; logistics efficiency index; transport potential; transit potential; transport network; логістика; логістична інфраструктура; індекс ефективності логістики; транспортний потенціал; транзитний потенціал; транспортна мережа